(untitled) (Bangladesh Journal of Medical Science, 2023)
Objective: The aim of this paper was to describe work motivation of medical staffs and analyze some related factors. Materials and methods: The study was conducted in internal medicine departments of Kien Giang General Hospital on 384 subjects. Results and Discussion: Regarding the work motivation of medical staffs, the percentage of health workers with good motivation at work accounts for a fairly high rate of 72.9%. The highest achievement aspiration score (average 4.03 points versus maximum 5 points) the lowest was the motivation from recognition of achievement (3.76 points on average).The proportion of good comments about management and supervision factors of medical staff were lowest while satisfaction with management regime and remuneration policy is highest (53.4% and 81.2% respectively).In terms of some related factors to the work motivation of medical staff, positive attitude towards the prevention of the COVID-19 epidemic, good work motivation was 82.2% higher than that of the group of employees who werestill afraid of the disease: 69.6% (OR=2.01; p<0.05).The group that was satisfied with their personal income, the rate of good work motivation was significantly higher than the group of unsatisfied employees (OR= 3.11; p<0.001). Doctors had a higher percentage of good motivation than groups of nurses and technicians (OR = 3.03; p < 0.001). The group that was satisfied with the working conditions had a higher rate of good work motivation than those who were not satisfied with the working conditions (OR=6.59; p<0.001). The group that is satisfied with the management regime and policies, the rate of good work motivation is much higher than the unsatisfied group of employees (OR=17.92; p<0.001). The group with a positive attitude (supporting) work management and supervision had significantly higher rate of good work motivation than the group of employees with a negative attitude (OR=7.57; p< 0.001). Conclusion: The percentage of employees with good work motivation was quite high. The factors related to the strongest work motivation were meeting personal aspirations and interests, the responsibility for work and acceptance of the hospital’s management regime. The epidemic has affected the work motivation of medical staff (at the onset of the COVID-19 epidemic). Bangladesh Journal of Medical Science Vol. 22 No. 01 January’23 Page : 121-127